OPTIMALISASI PENGELOLAAN PERMINTAAN DAN PENDISTRIBUSIAN OBAT DI GUDANG FARMASI MELALUI DIGITALISASI BARCODE: ACTION RESEARCH DI RS YUKUM MEDICAL CENTRE - Nurbaiti; Fitri Yuli Mayasari; Fransiska Desi Natalia; Shinta Kurniasari; Kevin Fitrah Choirizaldi (Journal of Hospital Administration and Excellent Health Service, 2026)
Pharmaceutical logistics management plays an important role in ensuring service quality and patient safety in hospitals. Suboptimal logistics management can lead to stock mismatches, delays in drug distribution, and increased workload. This study aims to explore operational obstacles in the demand and distribution of drugs at Yukum Medical Centre (YMC) Hospital and to formulate practical optimization strategies. This study uses a qualitative method with a descriptive-analytical approach through an Action Research design. Data was collected through participatory observation, Focus Group Discussions (FGD), in-depth interviews, and review of logistics documents in April 2026. Analysis using the Urgency, Seriousness, Growth (USG) method and Fishbone Diagram identified that there is no structured routine request schedule, stock card recording is still manual, and there are limitations in the integration of the Hospital Information System (SIMRS). and inefficient warehouse organization is the root cause of the problem. As a practical solution, this study designs an intervention in the form of standardizing the depot unit request schedule and implementing GS1 DataMatrix barcode (2D barcode) based digitalization. This combination of interventions has the potential to significantly improve staff work efficiency, minimize administrative errors (human error), maintain real-time stock data accuracy, and support patient safety through reliable drug traceability. Keywords: barcode, distribution, innovation, pharmaceutical logistics, hospital.